Women's Needs on Bed Rest during High-risk pregnancy and Postpartum Period: A Qualitative Study - Moghgan Janighorban; Zeinab Heidari; Azam Dadkhah; Fatemeh Mohammadi (Mashhad University of Medical Sciences, 2018)
Background & aim: pregnancy is a normal part of life, however, high-risk pregnancy that need bed rest can be stressful and affect woman and her family. Therefore, understanding the needs of women on bed rest seems to be necessary to enhance the quality of care services. The present study was conducted to investigate the women's needs on bed rest during high-risk pregnancy and postpartum period. Methods: This qualitative study was performed among women with high-risk pregnancy using purposeful sampling method. Data were collected by conducting 31 semi-structured interviews with 21 pregnant women, 10 spouses, and 7 medical staff involved in their healthcare. Data analysis was carried out using conventional content analysis developed by Hsieh and Shannon. Results: According to the results, there were four main categories of needs entailing the need for psychosocial support, support for family and personal affairs, support for looking after children, and the need for economic support. The final category was the need for comprehensive support. Conclusion: The personal and family life of pregnant women is affected during bed rest. Accordingly, comprehensive support is needed to enable women to cope with these problems. To reach this goal, the provision of family-centered support services based on coordination among health sections, supporting organizations, charities, social workers, and systems providing psychological and consultation services are recommended.